DNA Double-Strand Break Repair: All Roads Lead to HeterochROMAtin Marks - Caron, Pierre; Pobega, Enrico; Polo, Sophie E. (Frontiers in Genetics, 2021)
In response to DNA double-strand breaks (DSBs), chromatin modifications orchestrate DNA repair pathways thus safeguarding genome integrity. Recent studies have uncovered a key role for heterochromatin marks and associated factors in shaping DSB repair within the nucleus. In this review, we present our current knowledge of the interplay between heterochromatin marks and DSB repair. We discuss the impact of heterochromatin features, either pre-existing in heterochromatin domains or de novo established in euchromatin, on DSB repair pathway choice. We emphasize how heterochromatin decompaction and mobility further support DSB repair, focusing on recent mechanistic insights into these processes. Finally, we speculate about potential molecular players involved in the maintenance or the erasure of heterochromatin marks following DSB repair, and their implications for restoring epigenome function and integrity.